1893 Or. Laws 79, An Act to Prevent a Person from Trespassing upon Any Enclosed Premises or Lands Not His Own Being Armed with§a Gun, Pistol, or Other Firearm, and to Prevent Shooting upon or From the Public Highway, §§ 1-3. - (:unkn) unknown (My University, 1893)
It shall be unlawful for any person, other than an officer on lawful business, being armed with a gun, pistol, or other firearm, to go or trespass upon any enclosed premises or lands without the consent of the owner or possessor thereof. § 2. It shall be unlawful for any person to shoot upon or from the public highways. § 3. It shall be unlawful for any person, being armed with a gun or other firearm, to cause, permit or suffer any dog, accompanying such person, to go or enter upon any enclosed premises without the consent of the owner or possessor thereof; provided; that this section shall not apply to dogs in pursuit of deer or varmints.
Keywords: COMMITTING CRIME W/ WEAPON; DISCHARGE